ANALISIS PREFERENSI KONSUMEN TERHADAP PRODUK KACANG SANGRAI DI UD. AL-MURTADHA KABUPATEN PAMEKASAN - Rusli, Moh.; Sustiyana, Sustiyana; Nazizah, Fitrotin (JURNAL AGROSAINS : Karya Kreatif dan Inovatif, 2023)
Peanut (Arachis hypogaea) is an agricultural commodity that is needed by the community, bothas human food and industrial raw material. This study aims to determine consumercharacteristics, product quality of roasted peanuts, analyze consumer preferences for theattributes of roasted peanut products. The method used in this research is descriptive analysis.Based on the results of the research and analysis that has been carried out, it can beconcluded that roasted peanut products with the "comfortable" brand are consumerpreferences at UD. Al-Murtadha, Pamekasan Regency, which has special characteristics interms of taste, quality, price, packaging and durability so that consumers agree with roastedpeanut products. Consumers are satisfied with the quality of roasted peanut products becausethey are different from other products so that consumers prefer products at UD. Al-Murtadha,Pamekasan Regency